The coordination of the European Union exploring the capacities of networked governance - Jordan, Andrew, 1968-; Schout, Adriaan, 1961-; Oxford eBooks (Oxford : Oxford University Press, 2006)
This work is an assessment of the coordinating potential of 'new' modes of governance in the EU. It attempts to develop policy coordination as new focus within EU scholarship and to invigorate and substantially re-orientate the theoretical debate about policy networks in the EU.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; Public administration -- European Union countries; Electronic books